The Use of The Quizizz Application in The Scientific Literacy Assessment of High School Students On Global Warming Material - Azuminatun Nadhifah; Mukhayyarotin Niswati Rodliyatul Jauhariyah (Jurnal Ilmiah Pendidikan Fisika, 2021)
This research aims to describe the feasibility of the scientific literacy assessment instrument, describe the high school students’ scientific literacy profile on global warming material, and examine scientific literacy instruments' practicality. The research data was collected using scientific literacy instruments with 16 multiple choice and four essays and student response questionnaires. This research refers to the ADDIE model. The analysis data of this instrument's feasibility is viewed from five criteria: the logical and empirical validity of the items, reliability, difficulty level, and distinguishing power. Student response questionnaires analyzed using quantitative descriptive methods. The sampling technique selected randomly. This study's limited trial subjects were 24 physics education freshmen at one of the state university in Surabaya city to determine the feasibility of the scientific literacy assessment instrument. Thirty-three students of Class XI MIPA 3 at one of the private senior high schools in Krian is a field trial. The results showed that the scientific literacy assessment instrument was feasible, with 10 of the 20 items developed. The average achievement of students' scientific literacy as a whole was 38. While the students’ ability in each aspect, namely explaining scientific phenomena, designing and evaluating scientific investigations, and interpreting scientific data and evidence, is in a very low category, less than 50%. The practicality of the instrument developed with a value range of 62%-74% in a good category. This research can be used as an evaluation material in learning activities to be more effective and optimal in improving scientific literacy skills.